Crianças Transgênero: uma análise da produção científica brasileira dos últimos cincos anos - Silva, Jeanne Araújo e (2019)
This research aimed to carry out a study on the Brazilian scientific production of the last five years (2014-2018) with a focus on discourses on transgender children, aiming to understand the aspects and dimensions highlighted in the perception of this theme, thus fostering interdisciplinary dialogues with authors , scholars and with works published under the authorship of people from LGBT communities who portray moments experienced in childhood. The first chapter brings us a little history about the perception of childhood, about how societies gradually perceived the distinctions between children and adults from the Middle Ages to the present day. The second chapter illustrates the State of the Art on Brazilian research aimed at the transgender child and the third chapter develops discussions with the chosen texts to understand aspects and dimensions that are notorious in the experiences of transgender people. The methodology chosen was bibliographic research with a qualitative and quantitative nature that enabled us to gather: theses and dissertations available in the CAPES Thesis and Dissertations Catalog; journals in the SCIELO Electronic Library; annals of academic events that bring the theme of gender and sexuality to their discussions. We seek to organize the results of the chosen works with the intention of producing a source for new research. Interdisciplinary dialogues with scholars made it possible for us to realize that, among the perceptions about trans childhood, a point in common among the researches analyzed is the exclusion of the subject who does not fit into gender norms norms and it was also possible to notice that there are different ways of singular subjectivity in the face of sexuality and gender. Keywords: transgender-child; child sexuality-research; subjectivation.